PENGARUH WORD OF MOUTH, KUALITAS LAYANAN, KUALITAS PRODUK DAN LOKASI TERHADAP KEPUTUSAN PEMBELIAN PADA TOKO SURYA INDAH JOMBANG (Study Kasus Pada Konsumen Toko Surya Indah Jombang) - Afida Nur Uzma; Rois Arifin; M. Hufron (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACT The purpose of this research was to identify and analyze the influence of word of mouth, service quality, product quality and location toward customer purchasing decision at Surya Indah Shop, Jombang. The explanatory research was applied to quantitative approach. The method of the research was multiple linear regressions. The sample of the research was taken through slovin formula with accidental sampling technique to have the sample based on accidental condition. Therefore, the participant in this research was the people who met to the researcher accidentally and assumed as the data resource. The number of the respondent was 98 respondents as the sample of 4500 respondents as the population.The findings showed that the word of mouth has partially influence toward purchasing customer decision, service quality has significant influence on the purchasing decision, product quality and location has significant affect toward purchasing decision customer at Surya Indah Shop as well. In the other hand, the result simultaneous test displayed that the word of mouth, service quality, product quality and location. Keyword: word of mouth, service quality, service product and location